2021
DOI: 10.3390/jcm10091972
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolic Antioxidant 3,5-dihydroxy-4-methoxybenzyl Alcohol (DHMBA) Prevents Enterocyte Cell Death under Oxygen-Dissolving Cold Conditions through Polyphyletic Antioxidant Actions

Abstract: Cold preservation in University of Wisconsin (UW) solution is not enough to maintain the viability of the small intestine, due to the oxidative stress. The novel phenolic antioxidant 3,5-dihydroxy-4-methoxybenzyl alcohol (DHMBA) has dual properties to reduce oxidative stress, radical scavenging, and antioxidant protein induction, in other cells. This study was designed to determine whether DHMBA reduces cold preservation injury of enterocytes, and to identify the effector site. Enterocytes were subjected to 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In previous study, DHMBA has been found that from Pacific oyster, can alleviate the oxidation of cultured human hepatocytes mediated by Diphenyl-1-pyrenylphosphine, as well as induce the expression of antioxidant proteins in cells, thus protecting mitochondria to mitigate cold damage in intestinal cells. [14,35] Nrf2 is a transcription factor responsible for regulating redox levels in mammalian cells. [10,36] By promoting increased expression of its downstream antioxidant proteins, it increases the antioxidant capacity of the body, reduces the level of oxidative stress, and delays aging.…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, DHMBA has been found that from Pacific oyster, can alleviate the oxidation of cultured human hepatocytes mediated by Diphenyl-1-pyrenylphosphine, as well as induce the expression of antioxidant proteins in cells, thus protecting mitochondria to mitigate cold damage in intestinal cells. [14,35] Nrf2 is a transcription factor responsible for regulating redox levels in mammalian cells. [10,36] By promoting increased expression of its downstream antioxidant proteins, it increases the antioxidant capacity of the body, reduces the level of oxidative stress, and delays aging.…”
Section: Discussionmentioning
confidence: 99%
“…3,5-dihydroxy-4-methoxybenzyl alcohol (DHMBA), a novel amphipathic phenolic compound, was initially isolated from the Pacific oyster (Crassostrea gigas) with a characterization of antioxidant [9,10]. We used the synthesized DHMBA in the present study [12][13][14]. DHMBA was obtained from Watanabe Oyster Laboratory, Inc. (Hachioji, Tokyo, Japan).…”
Section: 5-dihydroxy-4-methoxybenzyl Alcoholmentioning
confidence: 99%
“…The novel phenolic antioxidant 3,5-dihydroxy-4-methoxybenzyl alcohol (DHMBA) was originally found in the Pacific oyster Crassostrea gigas [9,10]. DHMBA has dual properties to prevent oxidative stress as radical scavenging in several cells [9][10][11][12][13][14]. Interestingly, DHMBA is an outstanding peroxyl radical scavenger, being about 15 times and four orders of magnitude better than Trolox for that purpose in lipid and aqueous media, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel phenolic antioxidant 3,5-dihydroxy-4-methoxybenzyl alcohol (DHMBA) was originally isolated from Pacific oyster Crassostrea gigas [12,13]. DHMBA has dual properties to reduce oxidative stress, radical scavenging, and antioxidant protein induction in cells [12][13][14][15][16][17]. DHMBA has been shown to eliminate hydroxyl radicals and inhibits hepatocyte DNA fragmentation and cell death in vitro [14].…”
Section: Introductionmentioning
confidence: 99%